Two new synonyms in Himalayan Saussurea (Asteraceae) - Yuan, Qian; Chen, Yousheng (Phytotaxa, 2014)
Saussurea Candolle (1810: 156) is one of the largest genera in the tribe Cardueae (Asteraceae) which includes over 400 species (Lipschitz 1979; Shi & Raab-Straube 2011).